Flood hazards : impacts and responses for the built environment - Proverbs, David G. (Boca Raton, Fl. : CRC Press, 2012)
'A 360-degree view of the response to flood riskAs major flooding events around the world show, the impact of flooding on the built environment can cause widespread chaos. These flood events form part of a wider pattern of increasing flood frequency coupled with increased vulnerability of the built environment to flood hazard. Flood risk can unite or divide communities and the responses to potential risk can range from denial to perfect adaptation. Drawing on the experience of communities and experts, Flood Hazards: Impacts and Responses for the Built Environment offers guidance on managing urban flooding and flood risk. It brings together a diversity of viewpoints and experiences on flood impacts and responses from leading academics, flood restoration specialists, emergency responders, architects, planning consultants, insurers, policymakers, and community representatives. By including the perspective of the community and the views of households and businesses at risk, this volume makes a unique contribution to the literature on flood management.The chapter organization loosely corresponds to the phases of the disaster management cycle, covering emergency preparation and response; recovery, repair, and reconstruction; and mitigation and adaptation. Contributors examine the types of impacts and discuss forecasting and emergency warning. They describe processes and good practice in recovery of flood-damaged property from the perspectives of the insurance industry, restorers, and loss adjusters. The book also deals with business continuity, land-use planning, property-level and infrastructure protection, and urban drainage, looking at the regulation and design of the built environment as one way to reduce risk. A section on community response to flooding sheds light on the experiences of flood-affected families.Written for students, practitioners, and researchers in flood risk management, as well as for professionals who may encounter flood-related issues in the course of their work, this cross-disciplinary book makes a valuable contribution towards designing a future built environment that is more resilient to flood risk'--
'Preface As recent flooding events show worldwide, the impact of flooding on the built environment can cause widespread chaos. These flood event forms part of a wider pattern of increasing flood frequency coupled with increased vulnerability of the built environment to flood hazard. Arguably, in the developed world, there exists the technology to handle the vast majority of flood events either through built in resilience, prevention of small scale regular flooding or through prediction and evacuation during large scale disasters. However, events in the UK in summer 2007 and 2009 have revealed that, while agencies are well prepared and briefed for the majority of circumstances, flood victims remain unconvinced that the best actions have been taken. The debate around the role of government, insurer, property professional, NGO, coastal engineer and flood victim has been played out in the media. The idea for this book stemmed from the synergy developed within the EPSRC funded international network of experts in flood repair (www.floodrepair.net) which is led by the University of Wolverhampton. This unique network of academics, property stakeholders and restoration specialists together with the involvement of international experts provided a forum for exchange of ideas which has proved highly valuable. It emerged that flood management is constantly evolving and valuable experience has been gained in the emergency management, recovery and restoration processes in recent years. Some of this experience has yet to be captured in the literature. The aim of this book is to disseminate these discussions to a wider audience. Practitioners, researchers, restorers, insurers and policy makers discuss their perspective on the wide issues surrounding flood risk management in one unique'--
Includes bibliographical references and index.
Keywords: Flood control; Emergency management